Big Data in Spain - Ángel Valarezo-Unda; Teodosio Pérez-Amaral; Covadonga Gijón (International Telecommunications Society (ITS), 2015)
What if we ask ourselves about what is the operating system and the physical infrastructure behind tools, services and companies we use or just see almost every day, like Google, Yahoo, Bing, Amazon, Facebook, Twitter, LinkedIn, Netfix, etc. What does make possible the increasing accuracy of Google Translator, the appropriate recommendations of Amazon, the contact suggestions of LinkedIn, the Netfix's hit House of Cards (Carr, 2013). Of course we imagine something bigger than what we use at home or within a small company to play our day to day work (O'Reilly, 2010). Three goals have driven this work: build our own definition and understanding of Big Data phenomenon, getting experience at using available tools based on related technologies and obtaining an approach about how interested is Spain in dealing with the new challenges Big Data represents.
Keywords: 330